Separation and confirmation of nine Enterobacteriaceae strains that carry the bla(NDM-1) gene - LI, TIAN-JIAO (Exp Ther Med, 2015)
The aim of the present study was to confirm the existence of carbapenem-resistant Enterobacteriaceae carrying the bla(NDM-1) gene in clinics in Hainan province, China. Collected clinical bacterial isolates that were Enterobacteriaceae strains suspected of producing carbapenemase were used as experimental strains. Drug resistance to imipenem, meropenem and other antibacterial agents was tested. Imipenem/imipenem inhibitor (IP/IPI) E-testing was conducted to identify the bacterial strains that produced metallo-β-lactamases. The bla(NDM-1) drug resistance gene was amplified by polymerase chain reaction (PCR), and agarose gel electrophoresis (AGE) and sequencing were conducted to identify the products. The species of the strains carrying the bla(NDM-1) gene were determined using a biochemical identification system. Through the IP/IPI E-test, 21 of the 30 collected Enterobacteriaceae strains were found to be positive, indicating that 70% of the strains produced metallo-β-lactamases. Following bla(NDM-1) gene PCR amplification, AGE and sequencing tests confirmed that nine of the strains carried the bla(NDM-1) drug resistance gene. The biochemical identification system indicated that four of the strains were Klebsiella pneumoniae, two were Escherichia coli, two were Enterobacter cloacae and one was Enterobacter aerogenes. Drug susceptibility testing in vitro demonstrated that the strains were 100% resistant to a broad spectrum antibiotic plus lactamase inhibitor, cephalosporins and carbapenems. However, they had high sensitivity rates to polymyxin B and tigecycline of 100 and 88.9%, respectively. The sensitivity rate to amikacin was also high at 77.8%, whereas sensitivity to ciprofloxacin and gentamicin was moderate at rates of 44.4 and 33.3% respectively. This clinical study of Enterobacteriaceae strains that carry the bla(NDM-1) gene in Hainan shows a bacterial tolerance that is different from that in previous studies, which requires further in-depth study.